"Collective violence" and honour in Finland: a survey for professionals. Issue 4 (16th March 2018) - Lidman, Satu; Hong, Tuuli
Abstract : Purpose: The purpose of this paper is to report on how honour-related violence (HRV) is understood and managed by professionals in Finland, emphasising the need to consider collectivity as an influential factor. Therefore, this paper introduces the concept of "collective violence". By investigating the level of awareness and recognition of these violence phenomena, this paper discusses both preventative and punitive measures that Finnish authorities are able to work with. Design/methodology/approach: A total of 111 Finnish anti-violence professionals completed a survey that aimed to qualitatively investigate their perceptions of HRV and collectivity. Findings: The findings of this study indicated that collective violence is generally poorly recognised among professionals in Finland. At present, both victim services and criminal justice system lack adequate structures to deal with issues of collective violence. These findings indicate that authorities need further education on HRV and collectivity, as well as debates on whether the criminal code should be amended to meet international requirements. Originality/value: As this violence has been researched only sporadically in the Finnish context, this study provides new insight to under-researched area of honour-related and collective violence in Finland. These findings may assist other European countries dealing with similar issues as well as guiding preventative and punitive measures within the Finnish context.